Chapter Il design sistemico per la valorizzazione del patrimonio faristico italiano - Grigatti, Gianluca (Proceedings e report, 2020)
This paper focuses on the Mediterranean coastal monitoring actors (i.e. maritime signaling instruments) such as lighthouses, lights, traffic lights. A twofold motivation behind this choice: on the one hand the 110th anniversary - that will be celebrated in 2021 - of the transfer of the management of the lighting service of the coasts from Italian Ministry of Public Works to the Navy. On the other hand, the willing to illustrate how the Systemic Design methodology can represent a strategic element for the enhancement of a coastal Cultural Heritage such as the one represented by lighthouses.